Health promotion of nursing staff in hospital environments - Laura Andrian Leal; Silvia Helena Henriques Camelo; Fernanda Ludmilla Rossi Rocha; Thamiris Cavazzani Vegro; Fabiana Cristina Santos (Rev Rene, 2015)
Objective: To analyze the scientific evidence of the strategies adopted by hospitals aimed at promoting the health of nursing workers. Methods: integrative review with data collected in electronic databases: Medline, Lilacs, Scielo, BDENF, Scopus and CINAHL, with the descriptors: Strategies; hospitals; Nursing and Health Promotion Team. Results: there were 18 articles selected and the analysis allowed to find organizational strategies to promote the health of nursing workers as prevention of biological risks, the use of personal protective equipment, among others. Conclusion: strategies for health promotion are possible as necessary and they should be reconsidered by managers and professionals working in hospitals in order to promote the quality of working life.